Spatial Integration for Assessing Land Condition in the Sileng Sub-Watershed, Magelang Regency: Integrasi Spasial untuk Penilaian Kondisi Lahan pada Sub-DAS Sileng, Kabupaten Magelang - Tri Sulistyo, Aprilian; Arbiwati, Dyah; Nurcholis, Mohammad (Jurnal Ilmu Tanah dan Air, 2024)
Land degradation in upland sub-watersheds poses serious threats to environmental sustainability, agricultural productivity, and disaster risk. This study aims to evaluate the land condition of the Sileng Sub-Watershed in Borobudur District, Central Java, using an integrated approach based on four key indicators: erosion index, land cover index, land use suitability, and landslide susceptibility. Field surveys and spatial analyses were conducted in 18 land system units, with supporting data derived from Sentinel-2 imagery and regional spatial planning maps. The results show that 61.1% of land systems are in good condition, 33.3% in fairly good condition, and 5.6% in moderate condition. While erosion risk is generally low, two land systems show critical erosion and landslide susceptibility due to steep slopes and minimal vegetative cover. The high land use suitability (88.36%) indicates strong adherence to spatial planning regulations, while the land cover index (63.71%) suggests moderate vegetation density. Overall, the integrated land condition index highlights both areas of ecological resilience and zones requiring rehabilitation. These findings offer valuable insights for sustainable watershed management and policy formulation, particularly in tropical highland areas vulnerable to land degradation and climate impacts.